Effects of Initial Soil Moisture, Clod Size, and Clay Content on Ammonia Volatilization after Subsurface Band Application of Urea. Issue 3 (1st May 2019) - Pelster, D. E.; Watt, Devon; Strachan, Ian B.; Rochette, P.; Bertrand, N.; Chantigny, M. H.
Abstract : Ammonia losses from broadcast urea vary based on soil physical and chemical properties; however, less is known about how soil properties affect NH3 losses after subsurface banding of urea. Therefore, three field trials were established to determine how initial soil moisture, clod size, and clay content affect NH3 volatilization from subsurface‐banded (0.025‐m depth) urea using wind tunnels. The first study measured volatilization after banding in a loamy mixed frigid Typic Humaquept at 50, 100, 150, 200, or 250 g kg −1 gravimetric water content (WC). Study 2 measured volatilization from the same soil after covering the bands with soil clods that ranged from <2 to >24 mm in diameter, whereas Study 3 measured volatilization from transplanted, acidic soils with clay contents ranging from 5 to 57%. Cumulative 17‐d NH3 losses for study one ranged from 8.3 to 20.8% of applied N, with the soil wetted to 200 g kg −1 WC experiencing the greatest losses. For Study 2, cumulative NH3 volatilization losses ranged from 10.8 to 20.8% of applied N, with the greatest losses from the largest clod sizes. For Study 3, NH3 losses ranged from 2.5 to 51.7% of applied N, with the NH3 losses correlated to the maximum pH measured in the band ( P < 0.001), and to the soil cation exchange capacity ( P = 0.054), titratable acidity ( P = 0.072), and clay content ( P = 0.100). However, the soil with high silt, not sand, content had the highest volatilization losses, suggesting that high silt soils may have the greatest potential for NH3 volatilization. Core Ideas: Greater NH3 losses from soils at 200 g kg −1 water content than at ≤150 g kg −1 . Covering the urea band with clods <6 mm reduced NH3 losses. Soil NH3 losses correlated closely to the maximum pH reached in the band and soil CEC. The highest NH3 losses were from soils with low clay and high silt content. Previous Canadian studies on NH3 loss from banded urea may overestimate losses.